Cashier App Revolutionizes Internal Controls in Global Enterprises: Aplikasi Kasir Merevolusi Kontrol Internal di Perusahaan Global - Pramudita, Rifkiansyah Aryasatya; abidin, Fityan izza noor (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the effectiveness of cashier application-based cash receipt systems as internal controls in small-scale enterprises, focusing on Lugo Coffee House in Tulungagung, Indonesia. Through qualitative analysis of interviews, observations, and document reviews, the study examines the functionality and integration of internal controls within these systems. Findings indicate that while the systems demonstrate efficiency in transaction processing and record-keeping, deficiencies such as the absence of task segregation pose potential risks. Nonetheless, the overall sufficiency of these systems in mitigating financial risks is affirmed. The study highlights the importance of optimizing cashier application-based systems to enhance financial management practices and minimize risks associated with cash transactions in similar organizational contexts. Highlights: 1. Assessing cashier app systems in small enterprises.2. Identifying internal control strengths and weaknesses.3. Optimizing financial management to minimize risks. Keywords: Cashier application, Internal controls, Small-scale enterprises, Financial management, Risk mitigation.